2020
DOI: 10.1002/cctc.201902241
|View full text |Cite
|
Sign up to set email alerts
|

High Catalytic Activity of Crystalline Lithium Calcium Silicate for Oxidative Coupling of Methane Originated from Crystallographic Joint Effects of Multiple Cations

Abstract: The oxidative coupling of methane (OCM) to C2 hydrocarbons is one of the most attractive catalytic processes towards the effective utilization of methane. Despite a great deal of effort in past research, the primary activation factor for OCM has still been unclear because of the chemical and structural complexities of known catalysts such as Mn−Na2WO4/SiO2. Here, we report a high catalytic activity of a crystalline oxide Li2CaSiO4 for OCM. The C2 selectivity and CH4 conversion reach 77.5 % and 28.3 %, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…215 Highly crystalline Li 2 CaSiO 4 has been proposed with high stability at 750 1C in the OCM reaction with a C 2+ selectivity of 77% and a CH 4 conversion of 28%. 203 2.4.1.2. Transition metal oxides.…”
Section: Methane Couplingmentioning
confidence: 99%
“…215 Highly crystalline Li 2 CaSiO 4 has been proposed with high stability at 750 1C in the OCM reaction with a C 2+ selectivity of 77% and a CH 4 conversion of 28%. 203 2.4.1.2. Transition metal oxides.…”
Section: Methane Couplingmentioning
confidence: 99%
“…Due to the poor stability of these Li-supported catalysts, some researchers have recently focused on depressing Li-ions' evaporation at high temperatures. Matsumoto et al [48] proposed that the catalytic activity and selectivity towards desired products were higher over crystalline Li 2 CaSiO 4 than Mn-Na 2 WO 4 /SiO 2, which is considered a state-of-the-art catalyst for OCM. The CH 4 conversion and C 2 selectivity were obtained at 28.3% and 77.5%, respectively, at the temperature of 750 • C for the OCM reaction.…”
Section: Alkali/alkaline Earth Metal Doped/supported On Metal Oxide Catalystsmentioning
confidence: 99%
“…As per the previous results, we understand that the mixed-phase oxides have multiple elements with an interface that are believed to show higher activity and stability due to the synergistic effect between the metal oxides. For example, when used Li doped TbO x and Sm 2 O 3 supported on MgO and they found that the Li-Tb 2 O 3 /n-MgO catalyst exhibited higher stability and lower deactivation rate after 30 h on stream [49], while Li 2 CaSiO 4 showed the better catalytic activity and selectivity over Mn-Na 2 WO 4 /SiO 2 and also exhibited higher catalyst durability for 50 h on stream without deactivation and structural changes for the OCM reaction [48].…”
Section: Alkali/alkaline Earth Metal Doped/supported On Metal Oxide Catalystsmentioning
confidence: 99%
“…[21] Although machine learning and data mining open up the insight on a powerful strategy for designing catalysts, [17][18][19][20][21] catalyst design on the basis of chemical and structural roles in the OCM reaction must be important from the fundamental point of view. Recently, Matsumoto et al [22] investigated the construction of well-defined active sites focusing on phase-pure crystalline oxides and discovered a quasi-ternary oxide Li 2 CaSiO 4 as a highly active OCM catalyst. They also emphasized the advantages of single-phase catalysts for mechanistic study.…”
Section: Introductionmentioning
confidence: 99%